The enhancement of Putra LRT information services: The usability testing of mobile Putra LRT - S. Omar, Mohamad Al-Bashir; Zainal Abidin, Ahmad Hisham (2006)
This research used the System Development Life Cycle Methodology (SDLC) as a guideline.The goal of this research project is to develop Mobile Putra LRT Information Services using Wireless Application Protocol (WAP) technology that supports the use of smart phones devices for the benefit of the public.A brief overview of several mobile technologies is presented. The development process and problems encountered when designing the prototype of the Putra LRT WAP is discussed in this paper.The usability testing conducted in this research revealed that the WAP site application is effective and should be implemented for Putra LRT system.